(3EbJUGO GdeDSSI (B/s - (3UNQj, eMeOs ((3GdLRGFQ(B: s (3OjhGf GdeWHhYGJ GdLGeYjI(B, s, 2007)
(3eGgjI heaghe GdEbJUGO hEbJUGO GdeDSSI hHYV GdeaGgje GdGSGSjI(B- (3GdbVGjG GdEbJUGOjI GdGSGSjI hCSGdjH eYGdLJgG(B- (3eGgjI heaghe GdeDSSI GdEbJUGOjI hCfhGYgG hNUGFUgG(B- (3JfXje GdeDSSI hEOGQJgG(B- (3QCSeGd GdeDSSI(B- (3fXQjI GdEfJGL(B- (3JcGdja GdEfJGL aj GdeDSSI(B- (3GdJNRjf hJMOjO MLeg(B- (3JbOjQ eHjYGJ GdeDSSI(B- (3JNWjW GdbhI GdYGedI(B- (3GdJfXje GdeGdj ddeDSSI(B- (3HYV eDTQGJ aYGdjI Ch COGA GdeDSSI GdEfJGLjI hGdYhGed GdeDKQI ajgG(B.s
Keywords: (3EbJUGO GdeDSSIs; (3GdEbJUGOs